2019
DOI: 10.29252/jhehp.5.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effects of Lactobacillus acidophilus and Lactobacillus reuteri against Campylobacter jejuni in Fresh and Roasted Chicken Breast Fillets

Abstract: Journal homepage: www.zums.ac.ir/jhehp Background: The present study aimed to determine the antimicrobial effects of Lactobacillus acidophilus and Lactobacillus reuteri against Campylobacter jejuni in fresh and roasted chicken breast fillets. Methods: Fresh and roasted chicken breast fillets were soaked in probiotic suspensions (11 log CFU/ml) and immersed in C. jejuni suspension (5 and 3 log CFU/ml). Afterwards, the fillets were placed in clean stomacher bags and refrigerated for 10 days until further analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Our study showed inhibitory effects of CFSs, obtained from the Lactobacillus species on C. jejuni isolate in human adenocarcinoma (HT-29) cell culture, mimicking host conditions. Numerous studies have reported that L. acidophilus, L. gasseri, L. fermentum, L. johnsonii, L. reuteri, L. crispatus, L. paracasei, L. plantarum, and L.salivarius or their cell-free supernatants repress the growth of the Campylobacter species (15,(27)(28)(29)(30)(31)(32). Consistent with previous results, our findings showed that at the first four hours of incubation, the growth of C. jejuni RM1221 was reduced by all lactobacilli CFSs, while C. jejuni 81116 was only significantly reduced by La and Lp CFSs in HT-29 cell cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed inhibitory effects of CFSs, obtained from the Lactobacillus species on C. jejuni isolate in human adenocarcinoma (HT-29) cell culture, mimicking host conditions. Numerous studies have reported that L. acidophilus, L. gasseri, L. fermentum, L. johnsonii, L. reuteri, L. crispatus, L. paracasei, L. plantarum, and L.salivarius or their cell-free supernatants repress the growth of the Campylobacter species (15,(27)(28)(29)(30)(31)(32). Consistent with previous results, our findings showed that at the first four hours of incubation, the growth of C. jejuni RM1221 was reduced by all lactobacilli CFSs, while C. jejuni 81116 was only significantly reduced by La and Lp CFSs in HT-29 cell cultures.…”
Section: Discussionmentioning
confidence: 99%